PENGARUH SUBSTITUSI PISANG GOROHO DAN KACANG MERAH TERHADAP KUALITAS FISIK, KIMIA DAN SENSORIS FLAKES UBI JALAR KUNING (Ipomoea batatas L.) SEBAGAI MAKANAN BEBAS GLUTEN BEBAS KASEIN - Tarigan, Andrea M.; Nurali, Erny J. N.; Taroreh, Mercy (Fakultas Pertanian, Universitas Sam Ratulangi, 2019)
Abstract This study aims to obtain the formulation of yellow sweet potato flour, goroho flour and red kidney bean flour in making the right flakes in terms of physicochemical characteristics, sensory characteristics and to calculate the calorific value of flakes. This study uses a completely randomized design with the comparison of yellow sweet potato: goroho plantain: red kidney bean is A = 50% + 40% + 10%; B = 60% + 30% + 10%; C = 70% + 20% + 10%; D = 80% + 10% + 10%. The parameters tested were chemical properties (moisture content, ash content, protein, fat, carbohydrate and crude fiber), calories, physical properties (color, fracture and crisp resistance in milk) and sensory properties (color, taste, aroma and texture). The best flakes in terms of their chemical composition were formulation A (50% yellow sweet potato flour + 40% goroho flour + 10% red kidney bean flour). Flakes that have the best physical properties are formulation C (70% yellow sweet potato flour + 20% goroho flour + 10% red kidney bean flour). The formulation of flakes which is most preferred by panelists is formulation C (70% yellow sweet potato flour + 20% goroho flour + 10% red kidney bean flour). The total number of calories in flakes ranges from 290,35 – 342,51 Cal.Keywords: Flakes, yellow sweet potato, goroho plantain, red kidney bean